Impact of Procedural Variation in Endoscopic Dilation for Idiopathic Subglottic Stenosis - Santapuram, Pooja; Tierney, William S; Huang, Li-Ching; Chen, Sheau-Chiann; Berry, Lynn D; Francis, David O; Gelbard, Alexander (The Laryngoscope, 2024)
A small number of Idiopathic subglottic stenosis (iSGS) patients are treated at institutions across the country. Divergence in operative techniques for endoscopic dilation (ED) of iSGS has been anecdotally recognized but not formally characterized. Additionally, the relationship between procedural variation and clinical outcome has not been studied. Secondary analysis of the NoAAC iSGS cohort investigated variation in procedural techniques and treatment outcomes in patients treated with ED across high-enrolling treatment centers (enrolled >10 patients in PR-02 trial). Thirteen NoAAC centers each enrolled >10 patients treated with ED for a total of 281 subjects. There was significant variation in procedural details and rate of recurrence among institutions. Hierarchal cluster analysis revealed significant heterogeneity among institutions and clusters in all procedural variables. However, analysis demonstrated a transient delay in disease recurrence in cluster 2 which disappeared with longer longitudinal follow-up. Patient-reported outcome and peak expiratory flow data supported the potential benefit of the technical variation in Cluster 2. Distinct to cluster 2, however, was routine use of adjuvant triple medical therapy (proton pump inhibitor (PPI), antibacterial agent, and steroid inhaler). Both outcome and procedural technique vary among centers employing ED to treat iSGS. A transient delay in recurrence was observed among centers that routinely prescribed adjuvant medical therapy (antibiotic, inhaled corticosteroid, and PPI) to iSGS patients after endoscopic dilation, which was further supported by patient-reported data and peak expiratory flow data. Prospective studies are needed to understand the effects of adjuvant medical therapy on recurrence after endoscopic dilation. 4 Laryngoscope, 134:3260-3266, 2024.